The Effect of Service Quality and Customer Value Co-Creation on Mekaar Customer Loyalty with Customer Satisfaction as an Intervening Variable at PT Permodalan Nasional Madani Depok Branch - Budi, Setia (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study purpose to test the effect of service quality, customer value co-creation, and customer satisfaction on Mekaar customer loyalty. The population used in this study were all Mekaar customers of PT Permodalan Nasional Madani Branch Depok, who have done Top-Up at least 3 times totaling 16,307 customers, and the selected sample is 100 customers, using proportional random sampling technique. Data collection technique is done using online questionnaires. The analysis technique used is multiple linear regression analysis. The results of the study indicate that Service quality has a positive and significant effect on customer satisfaction, Customer value co-creation has a positive and significant effect on customer satisfaction, Customer satisfaction has a positive and significant effect on customer loyalty, Service quality has a positive and significant effect on customer loyalty, Customer value co-creation has a positive and significant effect on customer loyalty, Customer satisfaction can mediate the effect of service quality on customer loyalty, Customer satisfaction can mediate the effect of customer value co-creation on customer